Heart Failure: A Deficiency of Energy—A Path Yet to Discover and Walk - Ioannis Paraskevaidis; Christos Kourek; Dimitrios Farmakis; Elias Tsougos (Biomedicines)
Heart failure is a complex syndrome and our understanding and therapeutic approach relies mostly on its phenotypic presentation. Notably, the heart is characterized as the most energy-consuming organ, being both a producer and consumer, in order to satisfy multiple cardiac functions: ion exchange, electromechanical coordination, excitation–contraction coupling, etc. By obtaining further knowledge of the cardiac energy field, we can probably better characterize the basic pathophysiological events occurring in heart disease patients and understand the metabolic substance changes, the relationship between the alteration of energy production/consumption, and hence energetic deficiency not only in the heart as a whole but in every single cardiac territory, which will hopefully provide us with the opportunity to uncover the beginning of the heart failure process. In this respect, using (a) newer imaging techniques, (b) biomedicine, (c) nanotechnology, and (d) artificial intelligence, we can gain a deeper understanding of this complex syndrome. This, in turn, can lead to earlier and more effective therapeutic approaches, ultimately improving human health. To date, the scientific community has not given sufficient attention to the energetic starvation model. In our view, this review aims to encourage scientists and the medical community to conduct studies for a better understanding and treatment of this syndrome.